Linear Epidermal Nevus of the Oral Cavity: A Rare Diagnosis - Mariana Dutra de Cássia Ferreira Santos; Alexandre Scalli Mathias Duarte; Guilherme Machado Carvalho; Alexandre Caixeta Guimarães; Carlos Eduardo Monteiro Zappelini; Ana Cristina Coelho Dal Rio; Maria Elvira Pizzigatti Corrêa; Albina Messias de Almeida Milani Altemani; Ester Maria Danielli Nicola (Case Reports in Medicine)
Linear epidermal nevus is an uncommon diagnosis of benign lesions of the oral cavity. It is characterized by a congenital malformation arising from the ectoderm cells, which are arranged according to a typical linear configuration known as Blaschko’s lines. We report a case of linear epidermal nevus of oral cavity in a 51-year-old lady or woman. The linear epidermal nevus of the oral cavity, although rare, can be considered a differential diagnosis of oral papillomatosis (OP). The histopathological studies and detailed description are the center of the diagnostic and clinical evolution.